MATRIX ALGEBRA ALGORITHM OF STRUCTURE RANDOM RESPONSE NUMERICAL CHARACTERISTICS - Mei, Yulin (Chinese journal of mechanical engineering, 2003)
A new algorithm of structure random response numerical characteristics, named as matrix algebra algorithm of structure analysis is presented. Using the algorithm, structure random response numerical characteristics can easily be got by directly solvining linear matrix emmtions rather than structure motion differential equations. Moreover, in order to solve the conesponding linear matrix equations, the numerical integration fast algorithm is presented. Then according to the results, dynamicdesign and life-span estimation can be done. Besides, the new algorithm can solve non-proportion damp structure response.